Combined amplification and sound generation for tinnitus: a scoping review - Tutaj, Lindsey; Hoare, Derek J.; Sereda, Magdalena (Lippincott, Williams & Wilkins, 2017)
Objectives: In most cases, tinnitus is accompanied by some degree of hearing loss. Current tinnitus management guidelines recognize the importance of addressing hearing difficulties, with hearing aids being a common option. Sound therapy is the preferred mode of audiological tinnitus management in many countries, including in the United Kingdom.Combination instruments provide a further option for those with an aidable hearing loss, as they combine amplification with a sound generation option. The aims of this scoping review were to catalog the existing body of evidence on combined amplification and sound generation for tinnitus and consider opportunities for further research or evidence synthesis. Design: A scoping review is a rigorous way to identify and review an established body of knowledge in the field for suggestive but not definitive findings and gaps in current knowledge. A wide variety of databases were used to ensure that all relevant records within the scope of this review were captured, including gray literature, conference proceedings, dissertations and theses, and peer-reviewed articles. Data were gathered using scoping review methodology and consisted of the following steps:(1) identifying potentially relevant records; (2) selecting relevant records; (3) extracting data; and (4) collating, summarizing, and reporting results. Results: Searches using 20 different databases covered peer-reviewed and gray literature and returned 5959 records. After exclusion of duplicates and works that were out of scope, 89 records remained for further analysis. A large number of records identified varied considerably in methodology, applied management programs, and type of devices. There were significant differences in practice between different countries and clinics regarding candidature and fitting of combination aids, partly driven by the application of different management programs. Conclusions: Further studies on the use and effects of combined amplification and sound generation for tinnitus are indicated, including further efficacy studies, evidence synthesis, development of guidelines, and recommended procedures that are based on existing knowledge, expert knowledge, and clinical service evaluations.